A delayless subband active noise control system for wideband noise control. - Seon Joon Park
In this paper, we present an efficient noise control algorithm based on the delayless subband adaptive filter. The algorithm reduces the computational complexity of the delayless subband filter by decomposing the secondary path response into a set of subband functions. In this new algorithm, the filtered reference signal is generated for each subband by using a short impulse response filter that models the secondary path transfer function in a subband-decomposed form. Computational efficiency of the presented method originates from the fact that the filtering process occurs only in one subband for each reference input sample. Furthermore, computational efficiency is enhanced when the presented algorithm is combined with an online identification of the secondary path transfer function. We also propose a frequency-domain implementation of the presented algorithm. In this implementation, it is shown that the computational complexity is further reduced by employing the block-processing approach
Keywords: Block-processing approach; Computational complexity; Computational efficiency; Delayless subband active noise control system; Filtered reference signal; Filtering process; Frequency-domain implementation; Impulse response filter; Secondary path response; Secondary path transfer function; Subband functions; Wideband noise control